Dynamics, Problems, and Solutions in the Implementation of a Love-Based Curriculum as Reinforcement of the Merdeka Curriculum in the Deep Learning Approach - Husna Dzakia Aini; Ari Susetiyo (MEDIA DAN STRATEGI PEMBELAJARAN, 2026)
The transformation of education in the twenty-first century requires learning approaches that not only emphasize cognitive achievement but also foster character development and humanistic values. In Indonesia, educational reform has been implemented through the Merdeka Curriculum, which promotes student-centered learning, flexibility in instructional practices, and the development of the Pancasila Student Profile. In this context, the Love-Based Curriculum emerges as an innovative pedagogical approach that integrates empathy, compassion, and ethical values into the learning process. This study aims to analyze the dynamics, theoretical foundations, challenges, and strategic solutions related to the implementation of the Love-Based Curriculum in the context of the Merdeka Curriculum and deep learning approaches. The research employs a qualitative method using a literature review design by examining relevant national and international scholarly sources.The findings indicate that the integration of love-based pedagogy and deep learning can support meaningful and holistic learning by fostering students’ intellectual, emotional, and social development. The implementation of this approach also aligns with the principles of the Merdeka Curriculum, particularly in promoting student-centered learning and character education. However, several challenges remain, including limited teacher understanding of love pedagogy, assessment systems that focus primarily on cognitive outcomes, and institutional constraints within schools.To address these challenges, the study proposes several strategies, including strengthening teacher professional development, developing holistic assessment models, and fostering collaboration among schools, families, and communities. Overall, the Love-Based Curriculum offers a promising framework for supporting holistic education and character development in Indonesian educational contexts.